2021
DOI: 10.3390/jcm10194522
|View full text |Cite
|
Sign up to set email alerts
|

Personalization of Treatment for Patients with Childhood-Abuse-Related Posttraumatic Stress Disorder

Abstract: Background: Differences in effectiveness among treatments for posttraumatic stress disorder (PTSD) are typically small. Given the variation between patients in treatment response, personalization offers a new way to improve treatment outcomes. The aim of this study was to identify predictors of psychotherapy outcome in PTSD and to combine these into a personalized advantage index (PAI). Methods: We used data from a recent randomized controlled trial comparing prolonged exposure (PE; n = 48), intensified PE (iP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
3
10

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 57 publications
1
8
3
10
Order By: Relevance
“…Another explanation for this difference may be the study design. In contrast to our study, in which the number of trauma‐focused sessions for both conditions was the same, Hoeboer, Oprel, and colleagues (2021) offered fewer trauma‐focused sessions in the phase‐based condition than in the direct trauma‐focused condition. According to our results, the PAI analysis did not show significant differences between the two conditions with the same dose of trauma‐focused treatment or with the addition of STAIR in one of the two conditions.…”
Section: Discussioncontrasting
confidence: 91%
“…Another explanation for this difference may be the study design. In contrast to our study, in which the number of trauma‐focused sessions for both conditions was the same, Hoeboer, Oprel, and colleagues (2021) offered fewer trauma‐focused sessions in the phase‐based condition than in the direct trauma‐focused condition. According to our results, the PAI analysis did not show significant differences between the two conditions with the same dose of trauma‐focused treatment or with the addition of STAIR in one of the two conditions.…”
Section: Discussioncontrasting
confidence: 91%
“…Given the lack of differences in clinical outcomes (Oprel et al, 2021 ) and cost-effectiveness among treatments, as found in the present study, our findings leave room for shared decision making in choosing PTSD treatment, taking into account the preferences of patients and clinicians (Hamblen et al, 2019 ). Despite the lack of differences in clinical outcomes, it was previously found in the current study sample that several clinical predictors could indicate a more optimal treatment choice (Hoeboer et al, 2021 ). As such, personalization offers a promising method by which to assign patients to their optimal treatment (Deisenhofer et al, 2018 ; Keefe et al, 2018 ).…”
Section: Discussioncontrasting
confidence: 56%
“…Enhancement of these factors during therapy can lead to a more favourable outcome. Although our results require replication in future research, future modular and personalized treatments of PTSD should encompass therapy monitoring tools that allow for a rapid detection of disadvantageous idiographic therapy processes (Brintzinger et al, 2021;Cloitre et al, 2020;Hoeboer et al, 2021;. Furthermore, our results hint at the existence of a subgroup of patients with motivational, mindfulness, and self-care deficits who profit less from inpatient treatment.…”
Section: Summary Clinical Implications and Outlookmentioning
confidence: 60%